(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The changes that have occurred in the business environment and scientific and technological progress, as well as the complexity of administrative problems resulting from its practice of various activities, have led to an increase in the responsibilities entrusted to it, and for the purpose of achieving its strategic objectives, which has made the pillars of corporate governance an inevitable matter required by the nature of modern scientific management of the governorate, the success that companies seek is based on the fertile environment and the dialectical relationship between the individual and the company, and to achieve this success there must be a compatible and harmonious audit environment between the internal and external auditors, therefore, the research aims to reach to find the extent of the impact of the relationship between the internal and external auditor on the company’s business and results, to instill confidence in the financial reports, and to enhance the confidence of the founders, investors, relevant authorities and capital markets in the company, through the quality of the company’s profits. To reach the goal by testing the research hypotheses on a sample of companies listed in the Iraqi Stock Exchange for the period from 2010 to 2018 and by adopting the SPSS statistical method, to reach the goal by testing the research hypotheses on a sample of companies listed in the Iraqi Stock Exchange for the period from 2008 to 2018 and by adopting the SPSS statistical method, achieving quality profits, and vice versa.